Manajemen Proyek Program Perbaikan Mutu dan Kinerja melalui Audit Internal di Puskesmas Tanjung Api-Api - Rizky Putri Pratiwi; Siti Halimatul Munawarah; Rizma Adlia Syakurah (Prodi Kesehatan Masyarakat Fakultas Kesehatan Masyarakat UIN Sumatera Utara, 2024)
Public health centers as public providers are required to provide optimal services to the community. This research analyzes the quality and performance improvement program at the Tanjung Api-Api Public Health Center. This research uses a case approach through interviews, observation, and document review. The activities were carried out from January to April 2022. Informants in the research included the head of the public health center, program holders, implementers, and all of the staff at the Tanjung Api-Api. The results of the activities are processed and presented in descriptive form. This research uses a project management approach which consists of the activity initiation stage, preparation, implementation, monitoring and supervision, and evaluation. The results found that the registration process was still manual, the condition of service rooms was limited, the behavior of health workers was not good, and service times and infrastructure were incomplete. It is hoped that the public health center will immediately carry out follow-up actions to minimize various complaints so that people who receive services can feel satisfied and this will impact optimal quality and performance.Keywords: Health Service, Patient Satisfaction, Performance, Project Management, Quality Improvement